Comparative analysis of leakage current suppression capability of forward‐clamped and reverse‐clamped H10 three‐phase inverters - Haixiao Ma (Wiley, 2021)
Abstract Non‐isolated inverters have the disadvantage of large leakage current, which will damage the equipment and personal safety. In order to solve this problem, this paper proposes two H10 three‐phase inverter topologies named forward‐clamped and reverse‐clamped H10 inverters. Each of the topologies is composed of two DC bus switches, a clamping circuit and a traditional three‐phase inverter, but the clamping method of these two topologies is different. A general control strategy combining carrier modulation and logic operation for these two topologies are proposed. The control strategy allows the common‐mode voltage of these two topologies to vary between one third and two thirds of the DC bus voltage, but the frequency of the common‐mode voltage of the reverse‐clamped inverter is three times that of the forward‐clamped inverter. The loop impedance of the reverse‐clamped inverter increases significantly at high frequency, so the leakage current suppression capability is better. Simulation and experiment platforms of the inverter systems are built. The obtained results verify the correctness of the theoretical analysis.